Tropheryma whipplei infection presenting as indolent endophthalmitis - Rami Waked; Jeffrey K. Moore; Brandon Winward; Sophia Ham; Howard W. Hoyt; Leyla Azis (IDCases)
Tropheryma whipplei (T. whipplei) infection can be difficult to diagnose due to its variable clinical manifestations and the limitations of standard diagnostic tests. This case describes a 78-year-old male with blurry vision and floaters in his right eye five months after cataract surgery, along with new onset weight loss and arthralgias. Ophthalmologic examination revealed inflammation and posterior vitritis, and vitreous biopsy identified T. whipplei via broad-range bacterial PCR, despite negative vitreous cultures and unremarkable flow cytometry. Gastrointestinal endoscopic and cerebrospinal fluid studies revealed no pathological or molecular evidence of the disease, complicating the diagnosis. Treatment with intravenous ceftriaxone followed by oral trimethoprim-sulfamethoxazole for 12 months resulted in resolution of symptoms and inflammation, with normalization of laboratory markers. This case underscores the diagnostic utility of broad-range bacterial PCR in atypical infections and highlights Whipple infection as a differential diagnosis in ocular presentations. Comprehensive interdisciplinary evaluation was critical for effective management.